Chapter Introduction North and South in European and global social democracy - Granadino, Alan (Taylor & Francis, 2022)
"With a combined focus on social democrats in Northern and Southern Europe, this book crucially broadens our understanding of the transformation of European social democracy from the mid-1970s to the early-1990s. In doing so, it revisits the transformation of this ideological family at the end of the Cold War, and before the launch of Third Way politics, and examines the dynamics and power relations at play among European social democratic parties in a context of nascent globalization. The chronological, methodological and geographical approaches adopted allow for a more nuanced narrative of change for European social democracy than the hitherto dominant centric perspective. This book will be of key interest to scholars and students of social democracy, the European Centre-left, political parties, ideologies, and more broadly to comparative politics and European politics and history."